Electrification as a development and sustainability approach in rural areas using renewable energy sources - J. Fábregas Villegas; I. Tovar Ospino; A. Palencia Díaz (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: In the Colombian Caribbean, some rural communities rely on self-generated energy due to their lack of connection to the national grid. This energy generated is achieved through a combination of combustion engines and renewable sources. However, certain communities face challenges maintaining daily energy autonomy, resulting in developmental disparities. Consequently, the research aims to develop a strategy for assessing renewable resource availability and conducting risk analysis to support the implementation of electrification initiatives in rural areas of the Colombian Caribbean.METHODS: A review was made of the feasibility of financing projects with a focus on renewable energies by government financing entities in Colombia. Subsequently, risk management was applied in projects of this nature, assessing the renewable potentials available in the region, such as wind and photovoltaic solar energy.FINDINGS: Of the risks encountered, political risk is the main reason why projects focused on renewable energy in the Colombian Caribbean do not end in a good state of operation, although there is a good exploitable solar and wind energy potential in the region as indicated by the statistical analyses carried out with the records obtained by meteorological instrumentation of the area. Presenting potential solar radiation levels ranging from 5 kilowatt-hours per square meter per day, and wind speeds exceeding 2 and 7 meters per second in certain localities. This indicates that the signed projects are supported with inadequate dimensioning.CONCLUSION: The routes established to perform good management for the energization of these populations are presented, when evaluating the wind and solar potentials available by location, and the risk analysis which indicates that, for such proposals political and financial risks present the greatest uncertainty. The solar radiation potentials obtained are suitable for proper sizing of photovoltaic systems, and the wind speeds identified suggest a review of how to harness these wind potentials effectively.